2001
DOI: 10.1016/s1044-0305(01)00298-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray characterization of perrhenate systems

Abstract: The electrospray negative ion mode (ESI-) mass spectrometry study of freshly prepared perrhenate in the ammonium and alkali metal (Na and K) solutions has been detailed. The cone voltage dependency of the negative ion abundance clearly indicates that the collision-activated dissociation (CAD) process in the cone-to-skimmer region is the source for both linear and non-linear cone voltage dependencies. The model also highlights that the [ReO2]- and [ReO3]- ions observed in the ESI- spectra are not present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We have used the method of Sahureka et al 47 3are unreactive toward methane, ethene, methanol, and acetic acid (data not shown). Based on the estimates of the number density in the ion trap, this puts an upper limit of a reaction efficiency of less than one out of every 10 5 collisions with these neutral reagents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used the method of Sahureka et al 47 3are unreactive toward methane, ethene, methanol, and acetic acid (data not shown). Based on the estimates of the number density in the ion trap, this puts an upper limit of a reaction efficiency of less than one out of every 10 5 collisions with these neutral reagents.…”
Section: Resultsmentioning
confidence: 99%
“…39 In subsequent work, the metathesis reactions of the carbenes in ion-molecule reactions with vinyl ethers was studied, as illustrated for n-propyl vinyl ether in equation 5of Scheme 1. 40 With regards to the gas-phase chemistry of rhenium oxide anions, [44][45][46][47][48] the photoelectron spectroscopy of [ReO x ] -(x = 2-4) has been studied. 44,45 From these spectra the energy required to remove an electron [equation (6)], also defined as the electron affinity of the neutral [ReO x ], has been determined to be 2.5 eV for [ReO 2 ] -, 44 3.53 eV for [ReO 3 ] -, 45 and 5.58 eV for [ReO 4 ] -.…”
Section: Introductionmentioning
confidence: 99%